2017
DOI: 10.1371/journal.pone.0185163
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in carbon, nitrogen and phosphorus concentrations and C:N:P stoichiometry in different organs of a Larix principis-rupprechtii Mayr. plantation in the Qinling Mountains, China

Abstract: Understanding how concentrations of elements and their stoichiometry change with plant growth and age is critical for predicting plant community responses to environmental change. We used long-term field experiments to explore how the leaf, stem and root carbon (C), nitrogen (N) and phosphorous (P) concentrations and their stoichiometry changed with growth and stand age in a L. principis-rupprechtii Mayr. plantation from 2012–2015 in the Qinling Mountains, China. Our results showed that the C, N and P concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 50 publications
2
27
0
Order By: Relevance
“…Previous research indicated that increasing the N deposition can promote plant growth by improving the soil N supply, whereas increasing the P addition can stimulate the growth of plants limited by P deficiency [57]. We observed that different N and P addition treatments, along with seasonal changes, had measurable effects on the C:N:P stoichiometry in Chinese fir, which was reported in other species [58]. In summer, separate N or P addition did not affect the content and stoichiometry of C, N, and P in leaves; probably because of the relatively short treatment time, the nutrients were distributed with more priority to the roots than the aboveground organs, leading to no significant changes in the leaves.…”
Section: Seasonal Response Of Ecological Stoichiometry Under N and P supporting
confidence: 57%
“…Previous research indicated that increasing the N deposition can promote plant growth by improving the soil N supply, whereas increasing the P addition can stimulate the growth of plants limited by P deficiency [57]. We observed that different N and P addition treatments, along with seasonal changes, had measurable effects on the C:N:P stoichiometry in Chinese fir, which was reported in other species [58]. In summer, separate N or P addition did not affect the content and stoichiometry of C, N, and P in leaves; probably because of the relatively short treatment time, the nutrients were distributed with more priority to the roots than the aboveground organs, leading to no significant changes in the leaves.…”
Section: Seasonal Response Of Ecological Stoichiometry Under N and P supporting
confidence: 57%
“…Our results of diminishing nutrients such as C and N with leaf aging is in line with other studies ( Li et al, 2017 ), while other functional traits related to the stomata, such as STNR and SLA did not vary significantly along season. Another study on leaf traits of seven different woody species grown under experimental conditions shed light on their seasonal variation ( Römermann et al, 2016 ).…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, in coastal wetlands, LN of Suaeda salsa decreased significantly, while LC and LP did not change with the season in the Yellow River Delta, China [ 14 ]. In Qinling Mountains, LC of Larix principis-rupprechtii Mayr showed no significant seasonal change, while LN was highest in the summer and lowest in the autumn while LP decreased significantly from spring to autumn [ 15 ]. Seasonal variations in leaf stoichiometry of Carex brevicuspis in different altitude gradients of Dongting Lake were also observed.…”
Section: Introductionmentioning
confidence: 99%